2008
DOI: 10.1371/journal.pone.0002492
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutation in RNASEL Predicts Increased Risk of Head and Neck, Uterine Cervix and Breast Cancer

Abstract: The BackgroundRibonuclease L (RNASEL), encoding the 2′-5′-oligoadenylate (2-5A)-dependent RNase L, is a key enzyme in the interferon induced antiviral and anti-proliferate pathway. Mutations in RNASEL segregate with the disease in prostate cancer families and specific genotypes are associated with an increased risk of prostate cancer.Infection by human papillomavirus (HPV) is the major risk factor for uterine cervix cancer and for a subset of head and neck squamous cell carcinomas (HNSCC). HPV, Epstein Barr vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 48 publications
3
40
1
Order By: Relevance
“…SV40 T/t antigens have been shown to be related to the biological behavior and prognosis of breast cancer (1)(2)(3). In this study, we successfully established SV40 T/t antigen-induced breast cancer transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SV40 T/t antigens have been shown to be related to the biological behavior and prognosis of breast cancer (1)(2)(3). In this study, we successfully established SV40 T/t antigen-induced breast cancer transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although breast cancer is complex and highly variable in its clinical course, studies have indicated that SV40 T/t antigens are related to the biological behavior and prognosis of breast cancer (1)(2)(3). Previous studies have indicated that interleukins (IL1, IL2, IL12, IL15, IL18, IL24), tumor necrosis factor-α (TNF-α), and the interferon-γ (IFN-γ) can control the immune response and play an important role in breast cancer immunotherapy (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Because of steroid hormone regulation of prostate and breast cancers (16), we also considered implication of the genes within 1q25.3 in breast cancer development. Because mutation screening of RNASEL has not pointed at its unambiguous involvement in breast cancer, we have focused on the group of RGS genes from the region of interest (17,18). The novel family of RGS proteins plays an essential role in regulating GPCR-induced signaling by enhancing the GTPase activity, thereby attenuating the G protein-dependent activation cycle (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…RNase L also contributes to tumor suppressor activities such as stress mediated apoptosis cell proliferation and regulation of protein synthesis (Liang et al 2006, Madsen et al 2008. Mutated RNase L was related to the increased risk of head and neck, uterine cervix, breast and prostate cancer (Madsen et al, 2008;Carpten et al, 2002).…”
Section: Rnase Lmentioning
confidence: 99%
“…Mutated RNase L was related to the increased risk of head and neck, uterine cervix, breast and prostate cancer (Madsen et al, 2008;Carpten et al, 2002).…”
Section: Rnase Lmentioning
confidence: 99%